Frontal activity during a verbal emotional working memory task in patients with Alzheimer's disease: A functional near-infrared spectroscopy study. (30th March 2017) - Ateş, Fatma Ebru; Cangöz, Banu; Özel Kızıl, Erguvan Tuğba; Baskak, Bora; Baran, Zeynel; Özgüven, Halise Devrimci
Abstract: Emotional working memory (EWM) is suggested as a working memory (WM) type, distinguished to process emotional stimuli, and may or may not be spared in Alzheimer's disease (AD). The aim was to compare patients with AD and healthy older adults (HC) on verbal EWM performance and accompanying prefrontal cortex activity. Twenty AD patients along with 20 HC individuals are required to complete an emotional one-back task in three conditions (neutral, positive and negative word lists). Prefrontal oxyhemoglobin (oxyHb) concentrations were measured simultaneously by a 24- channel functional near infrared spectroscopy device. Correct response rates were similar in two groups in all conditions. Reaction times were comparable in the EWM positive condition but longer in the AD group in EWMneutral and negative conditions. In the HC group, emotional words had no significant effect on WM. On the other hand, positive compared to neutral words led to greater activation in the left ventral prefrontal cortex (VPFC) in AD group. When compared to HCs, activity in the VPFC was significantly higher in AD patients during the positive condition. Positive words facilitated WM performance in participants with AD. Activity in VPFC may be the functional correlate of this phenomenon. Abstract : Highlights: No difference between groups in terms of accuracy in positive condition (PEW). Alzheimer's patients are faster in PEW compared to negative condition (NEW). High activity is found in left prefrontal cortex in PEW condition. Activity in left prefrontal cortex may correspond to the positivity effect. Participants with AD performed as successfully as healthy old adults in WM task with positive words.